Life satisfaction, academic achievement and Work readiness among undergraduate students - Phyleecia Chong Sze Jing; Guan Teik Ee (Global Academic Excellence (M) Sdn Bhd (GAE), 2022)
Today's workplace needs highly skilled workers and work readiness is important as it is used to predict how much students perform in the future in terms of competency. Life satisfaction is a measure of quality of life and many studies show that it influences work readiness. As for academic achievement, the more students scored in the examination, indicating that they attain more knowledge and skills learned. In Borneo, there is still a lack of studies being carried out to investigate these three factors. Thus the aim of this study is to investigate the correlation between life satisfaction and work readiness; and academic achievement and work readiness. Two measures were used, i.e. Satisfaction with Life Scale (SWLC) and Work Readiness Inventory (WRI). As for academic achievement, cumulative grade point average (CGPA) of the past semester was used. The participants were 265 undergraduate students. Results showed that life satisfaction has a positive correlation with all aspects of work readiness except self-view. Results also showed that there was no significant correlation between academic achievement and work readiness with all the 6 aspects of work readiness. Academic achievement no doubt is important, but it does not have a correlation with work readiness in this study, suggesting that there are other variables, probably like on-site training such as practicum and internship are important to get students ready for work.